HUBUNGAN ANTARA TINGKAT PENDIDIKAN DAN PENGETAHUAN IBU RUMAH TANGGA DENGAN KEIKUTSERTAAN DALAM PEMERIKSAAN PAP SMEAR DI KELUARGA BINAAN KESEHATAN FK UMSU ANGKATAN 2017 - NABILA QISTHI AL KHEIRI NASUTION; RAHMANITA SINAGA (LP2MTBM MAKARIOZ, 2021)
Pap smear is an affordable and non-invasive examination to examine cells in the cervix uteri. There are many factors thatcan influence a person in conducting a pap smear examination, one of which is the level of education and knowledge. Thegeneral objective in this study is to relate the level of education and knowledge of housewives with participation in pap smearexaminations in the fostered families of FK UMSU 2017. Caterogical analytic using cross sectional design. Validatedquestionnaire with a total of 31 samples. Chi square test obtained p value = 0.020 (p <0.05) of education with pap smearparticipation and p value = 0.006 (p <0.05) of the level of knowledge with pap smear participation. Pap smear participationhave a correlation to education and level of knowledge.